THE TEMPORAL PERSPECTIVES IN FRANCIS BACON’S ESSAY “OF DELAYS”: A TEXTUAL ANALYSIS - Wiqar Ahmad; Mashal Ejaz; Dr. Humaira Riaz* (`, 2025)
The piece "Of Delays" by Francis Bacon presents valuable material for studying temporal perspectives through textual analysis methods, as described by Catherine Belsey (2013). Belsey’s method studies how multiple text significances form through historical and cultural scenarios. Bacon presents his pragmatic approach toward timing by investigating the contrast between haste and procrastination throughout his essay. The results show that Bacon supports the design of a situationalical framework to select appropriate timing for each circumstance. The classical references and historical advice in his arguments grant Bacon strong authority and simultaneously display the cultural context of the early 17th century. The research shows that Bacon’s thoughts about timing encompass issues that modern people face with time organization and deciding when to make important choices. Applying Belsey’s method enables us to understand how Bacon strategically employed language in his writing to deliver ageless knowledge about human actions. Bacon presents complex insights about time, which lead readers to learn how to effectively manage decision-making by uniting the traits of being prompt and patient in their activities. KEYWORDS: Multiplicity, Procrastination, Aphorisms, Temporal perspective.